Terapeutyczne aspekty wywiadu narracyjnego w perspektywie prowadzenia badań biograficznych - Karkowska, Magda (Studia Edukacyjne, 2018)
The article is devoted to an attempt to present a biographical approach in pedagogical research, taking into account not only exploratory but also therapeutic functions of narrative interviews. The reflections focus of looking for the answer to the question: whether and to what extent telling a story of one’s life (especially marked by traumatic experiences) may contribute to integrating the past and the present, increasing self-awareness, and thus (re-)constructing the narrator’s identity? I ask a question about the conditions to be met in order for the narrator to realize the limitations posed by the past and next to overcome the crisis by pointing out the main motives of action, epiphanies, crises, or breakthrough moments.